Assessing fiscal episodes - Afonso, António (2022)
In an OCDE panel, for the period 1970–2010, we assess the effects of fiscal consolidation episodes, with four different definitions. Our results reveal that lower final government consumption increases private consumption in three out of the four approaches, when a fiscal consolidation occurs, and the debt ratio is above the cross-country average. The magnitude of these coefficients is higher for countries with lower debt levels, implying more successful consolidations associated with reduced crowding-out effects. There is some evidence of non-Keynesian effects for both private consumption and private investment, and the effects of social transfers on private investment tend to be negative, both in the short and long run. In a financial crisis, such effects are also more prone to happen. Finally, raising long-term interest rates reduces per capita private investment